Optimization of the rearing environment for the black soldier fly, Hermetia illucens L. (Diptera: Stratiomyidae), a promising agent for organic waste bioconversion : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Manawatū, New Zealand - Liu, Zhongyi (Massey University, 2022)
Bioconversion is an environmentally, socially and economically sound measure for organic waste management. The black soldier fly (BSF), Hermetia illucens L. (Diptera Stratiomyidae), is one of the promising species for organic waste bioconversion. Larvae of BSF (BSFL) can feed on multiple types of organic waste, and the harvested larvae could be processed into valuable products such as animal feed, chitin, and organic fertilizer. To maximize the efficiency of a bioconversion system using BSFL, it is necessary to optimize the rearing environment of the insects, which requires knowledge of the impact of environmental factors on BSF at different life stages. This thesis reports my investigations on (1) the effect of diet on selected BSF larval (BSFL) life history and physiological traits and bioconversion efficiency, (2) the effect of substrate type and moisture content on BSF pupation, and (3) the effect of artificial light type, light regime, and adult density on BSF reproduction. First of all, I tested three types of organic waste (brewer’s waste, pig manure, and semidigested grass) against a standard diet (broll; a mixture of wheat bran and wheat flour). Among the organic wastes tested, brewer’s waste led to the fastest larval growth and highest larval weight gain. However, protein conversion efficiency of BSFL fed on brewer’s waste was lower than the larvae fed on the standard diet, which may be due to the high protein content in brewer’s waste. A meta-analysis revealed that dietary lignocellulosic content has an adverse impact on BSFL weight gain. Second, I investigated the effects of two pupation substrates (vermiculite and wood chips) and nine moisture levels on BSF pupation rate and depth. Using moist pupation substrate could reduce prepupal water loss, improve prepupal survival rate, and move forward the onset of pupation. BSF prepupae were found to stay at shallower depth levels when moisture content exceeded 20% and 70% for vermiculite and wood chips, respectively, which may be due to reduced oxygen availability. Third, I assessed four types of artificial light for their suitability of supporting mating of BSF from two different colonies. The artificial light that matches the spectral sensitivity of photoreceptors of BSF adults led to the highest mating success. Interestingly, artificial light resembling summer sunlight failed to support BSF mating, which may be due to its flickering. Colony effect was also significant on BSF mating success. Moreover, I found an interaction between the light regime and adult density on mean individual female reproductive output and adult survival rate. To optimize the reproductive output of a BSF colony, 8 h of photoperiod would be sufficient for a low adult density (e.g., lower than 800 individuals∙m−3), whereas longer photoperiods may be needed for higher adult densities. Finally, I present the implications that can be drawn from my findings, and my recommendations for future research and the relevant industry.
Keywords: Stratiomyidae; Reproduction; Infancy; Larvae; Food; Organic wastes; Recycling; 310913 Invertebrate biology; 410404 Environmental management